Akulturasi Hadis Dengan Tradisi Penyembelihan Hewan Pada Upacara Kematian Masyarakat Padang Bolak - Ilham Ramadan Siregar; Sri Wahyuni Hasibuan; Muslimin Muslimin (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
This study aims to describe the acculturation of Hadith and local culture in the tradition of slaughtering animals at death ceremonies preserved by the Padang Bolak Community, as part of a religious system that reflects the community's understanding of Hadith. This research is a field study using qualitative methods with the framework of living hadith theory. Research findings show that this tradition is a societal manifestation of the hadith that explains the Apostle's command, to feed the family of Ja'far bin Abi Talib on the day he was martyred at the battle of Mu'tah. Several hadiths became the theological basis for the implementation of this tradition, including the narrations of Abu Dawud (3132), Tirmidhi (998) Ibn Majah (1610) Ahmad (3: 280) from Abdullah bin Ja'far about the Apostle's command to make food for the family of Ja'far bin Abi Talib. This study concludes that the tradition of animal slaughter in the Padang Bolak community is an indirect reflection of the understanding of the hadith regarding the hadith of feeding the Ja'far family.